The impacts of COVID-19 on eating disorders and disordered eating: A mixed studies systematic review and implications - McLean, Courtney P.; Utpala, Ranjani; Sharp, Gemma (Frontiers in Psychology, 2022)
Purpose: The unique constraints to everyday life brought about by the COVID-19 pandemic have been suggested to negatively impact those with pre-existing mental health issues such as eating disorders. While individuals with eating disorders or disordered eating behaviours likely represent a vulnerable group to the COVID-19 pandemic, the impact of the pandemic is yet to be fully established. Methods: we systematically examined the impact of the COVID-19 pandemic on eating disorders and disordered eating behaviours. We searched electronic databases MEDLINE, PsycINFO, CINAHL, and EMBASE for literature published until October 2021. Eligible studies were required to report on individuals with or without a diagnosed eating disorder or disordered eating behaviours who were exposed to the COVID-19 pandemic. Findings: Seventy-two studies met eligibility criteria with the majority reporting an increase in eating disorder or disordered eating behaviours associated with the COVID-19 pandemic. Specifically, it appears children and adolescents and individuals with a diagnosed eating disorder may present vulnerable groups to the impacts of the COVID-19 pandemic. Discussion: This mixed systematic review provides a timely insight into COVID-19 eating disorder literature and will assist in understanding possible future long-term impacts of the pandemic on eating disorder behaviours. It appears that the role of stress in the development and maintenance of eating disorders may have been intensified to cope with the uncertainty of the COVID-19 pandemic. Future research is needed among understudied and minority groups and to examine the long-term implications of the COVID-19 pandemic on eating disorders and disordered eating behaviours.